Pengembangan Ilmu Agama Islam Dalam Perspektif Filsafat Islam: The Development of Islamic Religious Sciences from the Perspective of Islamic Philosophy - H. Syaiful (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2004)
The gap between the advancement of modern science and technology and the development of Islamic religious thought is a critical issue that requires a robust philosophical foundation. This article examines how the philosophy of science can serve as a conceptual framework for developing Islamic religious knowledge and as a perspective underpinning such development in the present and future. This library research employs descriptive and comparative methods for data collection, along with content analysis to interpret the meanings embedded in various philosophical perspectives on the development of Islamic religious knowledge. The findings reveal that the philosophy of science significantly contributes to the development of Islamic religious studies through its three main pillars: ontology, epistemology, and axiology. In conclusion, the development of Islamic religious knowledge requires the ability to understand classical texts alongside mastery of alternative critical-analytical thinking, as well as an ethical-philosophical approach that integrates doctrinal and historical-sociological perspectives. Fenomena ketimpangan antara kemajuan ilmu pengetahuan dan teknologi modern dengan perkembangan pemikiran keagamaan Islam menjadi isu krusial yang memerlukan landasan filosofis yang kokoh. Artikel ini mengkaji bagaimana filsafat ilmu dapat menjadi kerangka konseptual dalam pengembangan ilmu agama Islam, serta peran filsafat ilmu sebagai perspektif yang mendasari pengembangan tersebut di masa kini dan mendatang. Penelitian kepustakaan ini menggunakan metode deskriptif dan komparatif dalam pengumpulan data, serta analisis isi untuk menafsirkan makna dari berbagai pemikiran filosof tentang pengembangan ilmu agama Islam. Hasil penelitian menunjukkan bahwa filsafat ilmu memberikan kontribusi signifikan dalam pengembangan studi ilmu-ilmu keagamaan Islam melalui tiga pilar utama: ontologi, epistemologi, dan aksiologi. Kesimpulannya, pengembangan ilmu agama Islam memerlukan kemampuan memahami kitab-kitab klasik sekaligus penguasaan cara berpikir alternatif berbasis analisis kritis, serta pendekatan etis-filosofis yang mengintegrasikan pendekatan doktriner dan historis-sosiologis.